Intuitive Risk Information Display via Skin for Wearable Devices. Issue 4 (1st July 2020) - Kaiho, Yoshiyuki; Itoh, Toshihiro
Abstract : This study proposes and demonstrates the feasibility of an information presentation device that presents multiple stages of information intuitively through the skin of the wrist via electrical stimulation without causing pain. Previous research into tactile displays has found that complex stimulation is required to present absolute value information in multiple stages, which is difficult to recognize intuitively. To counter this problem, we introduce intuitive electrical stimulation to give a pulse-like sensation, which is an indicator of the physical condition. We examined the waveform conditions for recognizing the difference between five stages of heatstroke risk by pulse-like stimulation. In the state of being concentrated on the stimulation, it was possible for the subject to recognize the five stages with over 80% accuracy when the ratio of the stimulation period in two adjacent stages was set to 1.6 or more. However, in the state of doing other work, the subject's recognition rate decreased to 40% at the worst recognition in all stages when changing only the stimulation period. In contrast, it was found that when the current intensity and period of the stimulation were changed, especially such that the number of period steps per current intensity step is 3 or less, the difference in stages could be recognized with accuracy of 80% or more even in the state of doing other work.